The Effect of Fructose Addition in Semen Extender on Quality of Separation of Garut Ram Sperm in Several Storage Length - SD Rasad; LC Simanjuntak (Animal Production: Indonesian Journal of Animal Production, 2009)
The objective of the research were to find out the effect of fructose addition in semen extender to the quality of separation Garut ram sperm and their length viability (up to 40% motility) in cool storage. Research design was split plot with four treatments of fructose addition in coconut water extender as a main plot i.e.: 1% (P1); 1.25% (P2); 1.50 (P3) and 1.75% (P4) and the length of sperm viability in cool storage (0; 3rd ; 6 th;9 th;12 th and 15 th hour), as a subplot. Each treatment was repeated five times. Sperm separation was done by albumin column method with 10 % concentration in top layer and 30% in lower layer. Parameters of research were sperm motility and abnormality after separation. Research result showed that addition of 1.75% fructose has the best sperm motility of 57.18± 1.43% and abnormality of 5.76±0.20% in 12 hours cool storage (top layer of albumin column). Sperm motility of 57.62 ± 0.65 % and abnormality of 4.35 ± 0.25% in 12 hours cool storage (lower layer of albumin column). As a conclusion, addition of fructose in coconut water semen extender has positive influenced on sperm quality. (Animal Production 11(3): 196-201 (2009)Key Words: fructose, sperm quality, extender, Garut ram